RANCANG BANGUN APLIKASI PERMAINAN ADU CEPAT MEMBACA MENGGUNAKAN PERMAINAN MULTIPLAYER WORD SEARCH PUZZLE - Muhammad Sholeh; Erfanti Fakiah; Gilangsurya Adi P (Universitas Sahid Surakarta, 2018)
Various mcam mobile-based applications today are easily downloaded and played via mobile devices. One application that can be used is a game application, both gamesfor entertainment and games in which there is an element of education. With a megemas game that there is an element of education is expected, players, especially children in addition to getting entertainment also get education, Indirectly children learn and have to improve the ability that actually there element of education.This paper discusses the application of fast reading games by combining fast reading techniques and word search. This application is built using the JavaProgramming Language and the server is built with the Javascript Programming Language using the Node.js framework.Algorithm to solve game search word in this research using backtracking algorithm. To play this game requires two smartphone devices connected to each other,for that required media connection between devices ie the internet. The design and manufacture of this game aims to train the ability to read quickly as well asentertainment to fill the spare time.